Physical oceanography during HEINCKE cruise HE574 - Pogoda, Bernadette; Rohardt, Gerd (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, 2021)
Conductivity-temperature-depth profiles were measured using a Seabird SBE 911plus CTD during RV Heincke cruise HE574 between 12.04.2021 and 17.04.2021. Additional sensors included a WET Labs C-Star transmissometer and a WET Labs ECO-AFL fluorometer. Data were connected to the station book of the specific cruise as available in the DSHIP database. Processing of the data including removal of obvious outliers followed the procedures described in CTD Processing Logbook of RV Heincke (hdl:10013/epic.47427). A detailed report on the CTD data of HE574 is available at https://hdl.handle.net/10013/epic.7e2aff22-0a3b-4945-a6b4-4796811bb77e.
Keywords: CTD; HE574; Heincke